Análise de eficiência da atuação extrajudicial do Ministério Público do Trabalho - RODRIGO SILVEIRA XAVIER (2022)
Public policies are intended to materialize the citizens’ rights to government provisions. However, despite those constitutionally and legally provided rights, state omission and the consequent lack of implementation are still notorious (especially those regarding social rights, such as labor rights). This situation has motivated a growing number of judicial demands, generating a significant problem known as judicialization of public policies. In this context, seeking to contribute to increase further discussions about this subject, in view of society's desire for the realization of its rights and for the effective state action, the present work aimed to analyze the relative efficiency of all regional units of the Brazilian Labor Public Prosecution Ministry, in the extrajudicial control of the implementation of public policies in the different thematic areas. Through a quantitative-qualitative, descriptive and exploratory research, data from 2017 to 2019, provided by transparency portals, yearbooks published by National Council of the Public Prosecution Service and an internal statistical system called “MPT Gaia”, was systematized and interpreted. The study of such data was carried out using the technique of Data Envelopment Analysis (DEA), whose evidence was supported and complemented by critical analysis obtained through interviews with attorneys from the aforementioned ministerial institution. As a result, production frontiers were built and the relative efficiency levels of the regional units were identified, detailing the targets and references to be adopted in the benchmarking process. In general, it was found that the efficiency levels of the DMUs vary according to the subject under investigation, with some DMUs inefficient in general production, but efficient in specific areas and vice versa. However, it is noteworthy that the Regional Attorney of the 7th Region (Ceará, Brazil) and the Regional Labor Attorney of the 9th Region (Paraná, Brazil) manage to maintain a high and uniform performance, being efficient both in global production and in each of the nine areas themes throughout the analyzed triennium. It is expected to have added knowledge to the members of the organization and contributed to the increase of the institution’s general efficiency, which will help directing efforts in its finalistic performance, thus optimizing the realization of labor rights by avoiding the filing of conflicts that can be resolved more efficiently to society.